Cyanobacterial Diazotroph Distributions in the Western South Atlantic - Detoni, Amália Maria Sacilotto; Subramaniam, Ajit; Haley, Sheean T.; Dyhrman, Sonya T.; Calil, Paulo H. R. (Frontiers in Marine Science, 2022)
Inputs of new nitrogen by cyanobacterial diazotrophs are critical to ocean ecosystem structure and function. Relative to other ocean regions, there is a lack of data on the distribution of these microbes in the western South Atlantic. Here, the abundance of six diazotroph phylotypes: Trichodesmium, Crocosphaera, UCYN-A, Richelia associated with Rhizosolenia (Het-1) or Hemiaulus (Het-2), and Calothrix associated with Chaetoceros (Het-3) was measured by quantitative PCR (qPCR) of the nifH gene along a transect extending from the shelf-break to the open ocean along the Vitória-Trindade seamount chain (1200 km). Using nifH gene copies as a proxy for phylotype abundance, Crocosphaera signals were the most abundant, with a broad distribution throughout the study region. Trichodesmium signals were the second most abundant, with the greatest numbers confined to the warmer waters closer to the coast, and a significant positive correlation with temperature. The average signals for the host-associated diazotrophs (UCYN-A, Het-1, and Het-2) were consistently lower than for the other phylotypes. These findings expand measurements of cyanobacterial diazotroph distribution in the western South Atlantic, and provide a new resource to enhance modeling studies focused on patterns of nitrogen fixation in the global ocean.